Magnetic ordering in the Ising antiferromagnetic pyrochlore Nd2ScNbO7. (14th May 2021) - Mauws, C; Hiebert, N; Rutherford, M L; Zhou, H D; Huang, Q; Stone, M B; Butch, N P; Su, Y; Choi, E S; Yamani, Z; Wiebe, C R
Abstract: The question of structural disorder and its effects on magnetism is relevant to a number of spin liquid candidate materials. Although commonly thought of as a route to spin glass behaviour, here we describe a system in which the structural disorder results in long-range antiferromagnetic order due to local symmetry breaking. Nd2 ScNbO7 is shown to have a dispersionless gapped excitation observed in other neodymium pyrochlores below T N = 0.37 K through polarized and inelastic neutron scattering. However the dispersing spin waves are not observed. This excited mode is shown to occur in only 14(2)% of the neodymium ions through spectroscopy and is consistent with total scattering measurements as well as the magnitude of the dynamic moment 0.26(2) μ B . The remaining magnetic species order completely into the all-in all-out Ising antiferromagnetic structure. This can be seen as a result of local symmetry breaking due disordered Sc +3 and Nb +5 ions about the A -site. From this work, it has been established that B -site disorder restores the dipole-like behaviour of the Nd +3 ions compared to the Nd2 B2 O7 parent series.